Caracterização de Nanofios de ZnO sintetizados pelo método de oxidação térmica - CAMPOS, Alex da Cunha (2019)
The study of synthesis methods and physical properties of nanostructured transition metal oxides has attracted great interest in fundamental scientific research due to it’s potential technological applications. Among the various growth approaches, the thermal oxidation procedure is considered a simple, efficient and fast method that allows the obtaining of micro and nanostructured arrangements with controlled size and morphology. In particular, the occurrence of elongated nanostructures (with lengths greater than 10 μm and diameters less than 100 nm) is little mentioned in the literature when this method is used. In this study, long zinc oxide (ZnO) nanowires were obtained from the thermal oxidation of zinc metal plates (Zn) at temperatures above the melting point of the metal (TF ~ 420 ° C). The structural, morphological and elementar-composition characterization was performed through X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Dispersive Energy Spectroscopy (EDS) techniques, respectively. Measurements of γ-γ Perturbed Angular Correlation Spectroscopy (PAC) were also carried out to obtain information related to the defects and impurities in the synthesized samples. Specifically, for a sample submitted the a temperature at 620 ºC with a heating rate of 20 ºC min-1 the growth of long nanowires with a mean diameter of 74 nm, lengths of ~ 60 μm and high population density was observed. The results obtained from the heating of other samples at different rates increase of temperature indicate that this parameter is determinant in the adjustment of the morphology, size and density of ZnO nanowires. The growth mechanism of these elongated nanostructures is attributed to both by stress-induced diffusion processes and the vapor-solid dynamics of the atmosphere rich in zinc molecules. XRD measurements show patterns for ZnO and metalic Zn with preferred orientation, whereas PAC measurements using 111In(111Cd) indicate that the probe nuclei replace only the Zn crystallographic positions on metal zinc (oriented preferably). In samples heated to 820 and 1000 ° C, the DRX exhibits only a ZnO pattern. In contrast, PAC spectra continue to showing probe nuclei only at metalic Zn sites, indicating the presence of highly oriented Zn fine regions confined betwen ZnO grains, even after long periods of oxidation. These results show a strong potential of perturbed γ-γ Angular Correlation spectroscopy to reveal confined metalic regions and their orientation in the oxides matrix even when their concentration is extremely small for that XRD is able to detect them.